2020
DOI: 10.1126/scitranslmed.aba4448
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling across the nonalcoholic fatty liver disease spectrum reveals gene signatures for steatohepatitis and fibrosis

Abstract: The mechanisms that drive nonalcoholic fatty liver disease (NAFLD) remain incompletely understood. This large multicenter study characterized the transcriptional changes that occur in liver tissue across the NAFLD spectrum as disease progresses to cirrhosis to identify potential circulating markers. We performed high-throughput RNA sequencing on a discovery cohort comprising histologically characterized NAFLD samples from 206 patients. Unsupervised clustering stratified NAFLD on the basis of disease activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
301
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 284 publications
(322 citation statements)
references
References 53 publications
20
301
1
Order By: Relevance
“…Over recent years, high-through transcriptomic analyses have been used in efforts to examine changes that occur as NAFLD progresses [ Table 1]. Though some studies are limited to dichotomous comparisons between mild and advanced disease, the expression of HPC markers has been found to be enriched in more advanced stage of the disease [78][79][80][81][82][83][84] . In a small cohort of 22 patients with NAFLD or alcoholic liver disease, Starmann et al [78] reported the expression of KRT7, KRT23, and p62 to be enriched in steatohepatitis when compared to steatosis.…”
Section: Gene Signatures Of Advanced Nafldmentioning
confidence: 99%
See 4 more Smart Citations
“…Over recent years, high-through transcriptomic analyses have been used in efforts to examine changes that occur as NAFLD progresses [ Table 1]. Though some studies are limited to dichotomous comparisons between mild and advanced disease, the expression of HPC markers has been found to be enriched in more advanced stage of the disease [78][79][80][81][82][83][84] . In a small cohort of 22 patients with NAFLD or alcoholic liver disease, Starmann et al [78] reported the expression of KRT7, KRT23, and p62 to be enriched in steatohepatitis when compared to steatosis.…”
Section: Gene Signatures Of Advanced Nafldmentioning
confidence: 99%
“…K23 has been described as a stress-related DR marker associated with prominent inflammation and fibrosis in chronic liver disease, that can be induced in vitro by treatment with TWEAK and the type I acute phase inducer interleukin (IL)-1b [85] . Interestingly, other transcriptomics studies using larger NAFLD cohorts, have reported that the expression of TNF receptor superfamily member 12A (TNFRSF12A), the receptor for TWEAK, is increasingly expressed in advanced NAFLD [83,84] . Immunopositivity for TNFRSF12A in NASH has been described to be found in DR, endothelial cells and myofibroblasts [86] .…”
Section: Gene Signatures Of Advanced Nafldmentioning
confidence: 99%
See 3 more Smart Citations